Dynamic interactions of Trichoderma harzianum TS 143 from an old mining site in Turkey for potent metal(oid)s phytoextraction and bioenergy crop farming - Pehlivan, Necla; Gedik, Kenan; Eltem, Rengin; Terzi, Ertugrul (Elsevier BV, 2021)
Despite high pollution risk, the termination of mining practices is not in question in the current era in line with the growing needs of beings. Instead, the rehabilitation by phytoremediation restores the economic and aesthetic values of the damaged locale. Here, potentially toxic elements (PTEs) tolerant 29 Trichoderma isolates from mining sites located foothills of Turkey`s NE Black Sea coast were isolated. The highest tolerant strain (As 1400 mg L-1, Cd 1200 mg L-1, Cu 2000 mg L-1, Pb 2100 mg L-1, Zn 3000 mg L-1) was characterized with translation elongation factor1 alpha (tef-1α) barcode and deposited in the GenBank. The PTEs removal strength of novel Trichoderma harzianum TS143 was highest for Pb (58%) and the lowest for As (8.5%) in the order of Pb > Cd > Cu > Zn > As. While bioleaching capacity was highest in Cd with 30%, the lowest was for As (8%). TS143 was found remarkably effective on all the physicochemical parameters in the shoot and root tissues of maize. The increase in the carbohydrate content (33.50%) proves the potential usage of the contaminated maize plants in bioenergy production. Core sustainable agents with their mesh type robust hyphal structure enfolding PTEs such as TS143 contribute to the phytoremediation technology along with potential plant biomass management for the biodiesel industry.
Keywords: Trichoderma; Carbohydrate; Turkey; Agriculture; Maize; Phytoremediation; Soil; Biodegradation, Environmental; Biofuel; Metals, Heavy; Hypocreales; Soil Pollutants; Metal(oid) pollution; 2. Zero hunger; 7. Clean energy; 6. Clean water; 13. Climate action